Assessment of health-related quality of life among patients with non-communicable diseases - Nitin Kumar Joshi; Yogesh Kumar Jain; Varsha Joshi; Niraj Kumar; Jyoti Sharma; Pankaj Bhardwaj (International Journal of Public Health Science (IJPHS), 2021)
Non-communicable diseases (NCDs) are a global challenge towards diminishing quality of life. Health related quality of life (HRQoL) is a widely accepted measure of burden of disease for individuals with chronic conditions. Due to paucity of data in Western Rajasthan, India, this study was planned to assess the HRQoL due to NCDs in Jodhpur, India. A descriptive cross-sectional study was planned in government NCD center of Jodhpur. Convenience sampling was used to select 398 respondents and socio demographic data was collected. Short Form–36 (SF-36) questionnaire was used to measure perceived effects due to NCDs across eight domains of analyzed using descriptive and inferential statistics. High combined mean scores were obtained in domains of Social Functioning (77.87) and Mental Health (75.36%) and lowest scores for General Health (54.70%), Bodily Pain (60.06%) and Role Emotional (60.33%). Males recorded higher mean scores than females across all domains with high statistical significance for Bodily Pain, Vitality, Role Physical and Mental Health. Findings suggested worst and least affected domains of regular life functions due to NCDs. Greater focus on emotional distress, active inclusion of females in national health programmes and integration of NCD control program with Mental Health Program would aid to improve overall HRQoL in affected individuals.